2014
DOI: 10.1007/s12192-013-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

Five small heat shock protein genes from Chilo suppressalis: characteristics of gene, genomic organization, structural analysis, and transcription profiles

Abstract: Small heat shock proteins (sHSPs) are the most diverse but also the most poorly known family of molecular chaperones, and they play essential roles in various biological processes. The striped stem borer, Chilo suppressalis (Insecta: Lepidoptera: Pyralidae), is one of the most serious pests of rice, causing extensive damage and yield loss. In this study, we isolated and characterized five members of the sHSPs family-Cshsp19.8, Cshsp21.4, Cshsp21.5, Cshsp21.7a, and Cshsp21.7b-from C. suppressalis. The cDNAs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 61 publications
12
63
1
Order By: Relevance
“…Phylogenetic analysis of C. riparius sHSPs suggests the existence of three groups: one formed by CrHSP34 and CrHSP23, a second one formed by CrHSP21, and a third one comprised by the others. These results agree with previous data available for other species (Shen et al, 2011;Lu et al, 2014) which were used in the phylogenetic analysis (Supplementary material), suggesting a gradual emergence of new sHSP genes. However, comparison of individual evolutionary trees suggests that evolution of this family of genes may be more complex than previously thought and may involve several mechanisms depending on the species.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Phylogenetic analysis of C. riparius sHSPs suggests the existence of three groups: one formed by CrHSP34 and CrHSP23, a second one formed by CrHSP21, and a third one comprised by the others. These results agree with previous data available for other species (Shen et al, 2011;Lu et al, 2014) which were used in the phylogenetic analysis (Supplementary material), suggesting a gradual emergence of new sHSP genes. However, comparison of individual evolutionary trees suggests that evolution of this family of genes may be more complex than previously thought and may involve several mechanisms depending on the species.…”
Section: Discussionsupporting
confidence: 92%
“…The genes have been named according to the molecular weight of the predicted protein as CrHsp17, CrHsp21, CrHsp22, CrHsp23, CrHsp24, and CrHsp34. Previous studies in insects have identified several members of this family in different species (Li et al, 2009;Shen et al, 2011;Lu et al, 2014) including the sibling species Chironomus tentans (Vincent and Tanguay, 1979;Tanguay and Vincent, 1981) but there were differences in the number of representatives. In this study, we describe seven sHSPs in C. riparius, which is the same number proposed for A. gambiae and four less than for D. melanogaster (Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of A. nidulansshsp genes A) in different developmental stages, B) responding to thermal and cold stresses, C) responding to osmotic pressure and D) responding to oxidative stress. 2014; Chen and Zhang, 2014), and in Chilo suppressalis, Cshsp19.8 and Cshsp21.7b were both upregulated dramatically by heat and cold (Lu et al, 2014). In our study, all A. nidulans shsp genes but AN10507 were strongly induced when subjected to heat and cold pressure.…”
Section: Discussionsupporting
confidence: 52%
“…This phenomenon is due to that the female insects enter the adult stage in August (hot weather), whereas the male larvae continuously keep in the second‐instar stage. In kinds of moths ( Plutella xylostella , C. suppressalis and S. inferens ) , the lowest expression of hsp21.4 was observed in embryonic or larval stages, and the highest expression was found in adult stage (Chen & Zhang, ; Lu, Hua, Cui, & Du, ; Sun et al., ). Moreover, hsp21.4 was most strongly expressed in the head, gut or malpighian tubule of these moths, which all belonged to important detoxification tissues mainly because the sHSP could protect the insects from external injury in the adult stage (Lu et al., ; Sun et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the orthologous shsps , similar with the species‐specific shsps , could be classified into three types depending on the different reactions to the temperature stimuli. The first type, like Cshsp21.4 and Slhsp21.4 , was insensitive to heat or cold stress (Lu et al., ; Shen et al., ). And the second type can be upregulated under temperature stress conditions.…”
Section: Discussionmentioning
confidence: 99%